The Influence of the Regent's Policy on Duties and Functions of the Head of Service on the Loyalty of Smpn Teachers in Barat Pasaman Regency - Rudi Hasayangan; Nurhizrah Gistituati; Rusdinal; Hadiyanto (Researchparks Publishing, 2021)
Based on data from the Education Office of Pasaman Barat Regency, the number of SMPN teachers with the status of civil servants in Pasaman Barat Regency is 205 people and only 2 people get the rank of IV/b, while the amount teachers pile up in the rank of IV/a as many as 203 people. Furthermore, the Teacher Performance Assessment (UKG) of SMPN Pasaman Barat Regency was carried out by secondary education supervisors with a value of 36 from the ideal value of 56. The assessment consists of 14 items from 4 competencies, namely pedagogic, professional, social, and personality. Likewise, the UKG results carried out by the Ministry of National Education in 2012 obtained an average value of 49.22 which is ideally 70.00. Likewise, the average UN for the SMP level in 2015 only reached 4.35. This shows the low quality of teachers and instructors and is also influenced by the low level of teacher welfare. The study was conducted using path analysis with a total sample of 136. Research location in Pasaman Barat Regency. The population of SMP N teachers in the Pasaman Barat Regency is 205 people. The sampling technique is stratified random sampling using the Slovin formula. The level considered is the rank group, namely class III and IV, and is certified. The results showed that the Regent's policy had a significant effect on the loyalty of the duties and functions of the head of the service, but weak on teacher loyalty in SMP N Pasaman Barat Regency.